APLIKASI SISTEM PENGARSIPAN DOKUMEN MENGGUNAKAN METODE PROTOTIPE - Swanjaya, Daniel -; Arif, Muhammad Rizal (Nusanatara of Engineering, 2014)
AbstractArchivingdocumentsis an importantactivitythatshould bedone inanorganizationtosupportorganizational performanceintheareas of administration. Archivingprocessmust becarried outeffectivelyandefficientlyso thatdocuments canbestored securely, neatandeasy to find. Ittakesapplicationdocumentarchivingsystemthatcanfulfill the functionsofthe organization.Application developmentprocessis based ontheanalysis ofinformation systemdesignandmanufacturing cycle ofobjectorientedsoftwareengineeringusingtheprototypemethod.The studywill beconductedusing areferenceobtainedfromthe literatureabouttheapplicationarchivingdocumentswithsupporting datain the form ofwrittendocumentscontainedinInformaticsEngineering Programoffice.The dataconsistsofthe datacollectedletters,certificates, inventoryandother writtendocuments. While thereportgeneratedfromthis studyin the formofinventory isa document.The research activitieswill becarried outfor6monthsin accordancewiththe process ofmakingan applicationusingthestage ofmaking aprototypemethodthatincludesitsspecification, design, coding, andtesting.Whilethe outputgeneratedisanapplicationthatcan beusedbythe systemin the processofarchivingdocuments andscientificarticlesonthe applicationdocument archivingsystemusingthe prototype method.The results ofthis applicationis planned tobeimplementedinthe OfficeofInformaticsEngineeringDepartmentUniversity ofNusantaraPGRIÂ Keywords: archiving, document, prototype,administration, effective, efficient